Land Capability Evaluation of Upper Sekampung Watersheds - Banuwa, Irwan Sukri; Sinukaban, Naik; Tarigan, Suria Darma; Darusman, Dudung (UNIVERSITY OF LAMPUNG, 2008)
Land degradation is a serious problem in the Upper Sekampung Watersheds. This is because the farmers cultivated in steep land to coffee crops without in adequate soil and water conservation practices. The land degradation is mostly caused by erosion. The erosion problem not only stripping the most fertile top soil and decreasing crop production, but also resulting problems in lowland. Therefore, the reorientation land management should be improved to produce agriculture sustainability. The first step is to evaluated land capability this area. The objectives of the research were evaluate land capability of Upper Sekampung Watersheds. The results showed that the Upper Sekampung Watersheds were dominated with class and subclass land capability of III-l2 about 17.630,51 ha (41,58 %). All of the constrain for each land capability in this area is erosion hazard, especially land slope. From this research, cultivated land to coffee base crops were allowed in land capability II-l1.e1, III-l2, IV-l3, and VI-l4, with in adequate soil and water conservation practices. In contrary, the land capability of VII-l5 unsuitable for agriculture, they should be a nature or for conservation forest.